Avaliação de políticas públicas de saúde: em cena, o Programa Nacional de Melhoria do Acesso e da Qualidade na Atenção Básica (PMAQ-AB) - Maciel, Samara Souza (2021)
The central theme of this dissertation is primary health care policy evaluation processes, with a focus on pay-for-performance programs, addressing technical and socio-political aspects of the valuation field. The research assumes the objective of evaluate the National Program for Access and Quality Improvement in Primary Care (NPAQI-PC) in social-political attributes, from a document research supported by minutes of the National Health Council (NHC), and in its technical aspects, which are anchored in quantitative methods of impact assessment. The dissertation is reported in two articles and uses a mixed methodology to achieve its goals. The first chapter reports the systematic review of the literature, highlighting the gap in the research and corroborating its originality. It demonstrates search protocols and generalist information from the panorama of national and international publications. The second chapter presents the first article, whose methodology is qualitative and analyses deliberative processes within the scope of the National Health Council, regarding its approach upon the National Program for Access and Quality Improvement of Primary Care (NPAQI-PC), based on the Cycle and Public Policies model. It focuses on social-political aspects of the program, taking as an assumption that the NHC considers the NPAQI in its agendas and/or discussions, implementing the social control of the program, and deliberating on it, according to its attributions. The methodological procedure is focused on document research, through coding analysis in two cycles. The results demonstrate that the NHC addresses the NPAQI in their meetings in a predominantly indirect and organic way. The program is mentioned by the councilors in several discussions, indicating the Council’s concern about the quality of Primary Health Care (PHC) and its funding. The NHC addresses the NPAQI especially in its phase of implementation, indicating synergy among this program and other PHC's programs. The third chapter is a quantitative article, intending to identify the causal link between the implementation of the NPAQI in Brazilian municipalities and the results of the Sensitive Conditions Index to Primary Care (SCIPC). The research was conducted with secondary quantitative data available in the official platforms of the Federal Government to form a database to impact assessment, analyzed through the Difference-inDifferences method with multiple periods and event studies. The results show that the NPAQI has had impacts on the SCIPC, by helping to reduce hospitalizations sensitive to Primary Care, when controlled by socioeconomic factors, keeping everything as constant as possible.